Community Empowerment Using the ABCD Method to Utilize Inorganic Waste at UPT SMPN 31 Medan - Sibuea, Alya Az Zahra; Nasution, Amalia Rahmi; Amrainum, Desri; Yusrina, Tania; Hazrin, Yosi; Siregar, Putra Apriadi (PROMOTOR, 2025)
Waste management continues to be a significant challenge in major cities, including Medan City which generates 2,000 tons of waste daily. The types, quantities, and varieties of waste produced are steadily increasing due to annual population growth and evolving consumption patterns and lifestyle changes within the community. This community empowerment initiative aimed to enhance the knowledge and skills of students at SMPN 31 Medan. The study employed the Asset Based Community Development (ABCD) method. The program targeted 25 participants from Grade XI. Activities began with participants completing a pre-test, followed by material presentation by the research team, a post-test assessment, and culminated in hands-on recycling projects where students created piggy banks and pencil cases from used plastic bottles and straws. The program demonstrated significant success, evidenced by a 25.6-point increase in participants' knowledge scores and marked improvement in their inorganic waste recycling skills.